THE IMAGE OF WAR IN THE DIARY TEXT OF O. DOVZHENKO (on the 130th Anniversary of the Writer’s Birth) - Kosmeda, Tetyana (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. The research is conducted within the framework of the modern functionalpragmatic paradigm of knowledge, emphasizing the theory of ego-texts, or personal texts, and focusing on the theory of linguistic personality. Purpose. To model the image of the war with Nazi Germany from 1941 to 1945, as verbalized in O. Dovzhenko’s aphoristic collection, drawn from the discursive-textual space of his diary as a form of personal text. The author’s card index contains over 200 entries. Results. The image of war most vividly presents a binary opposition of “self” (the warrior-defender, the Ukrainian people as a whole) and “other” (the enemy, which may shift depending on time and circumstances). The war image is articulated through parameters such as its nature, scale, chances of victory or defeat, characterization of war agents, the moral and psychological state of society, its emotional and intellectual perception, and the heroism associated with war. Evidently, all wars share the same terrible and horrifying face, as verbalized in the discursive-textual space of O. Dovzhenko’s diary (the war with the Nazis, 1941–1945) and contemporary Ukrainian discourse during the Russian-Ukrainian war of the early 21st century. Originality. For the first time, the article presents a compiled and interpreted aphoristic collection from O. Dovzhenko’s diary, which conveys the image of war. It reveals the refined linguistic mastery of the writer in crafting aphorisms that emphasize intimate and nationally marked meanings, thoughts, intentions, and dreams, along with his intellectual-emotional capacity. The image of war depicted in O. Dovzhenko’s diary is an individual form of intellectual-emotional and aesthetic engagement with the wartime environment, forming an integral fragment of the author’s unique cognitive and linguistic worldview, imbued with a subjective axiological dimension. Conclusion. It has been demonstrated that the individualized artistic-documentary image of war, articulated in O. Dovzhenko’s diary, is based on a complex of associations and perceptions that arise within his linguistic consciousness to model intellectual-emotional meanings with evaluative significance. The writer’s aphoristic collection is shown to be crafted using vivid figurative techniques – metaphor, epithet, oxymoron, antithesis—enhanced by the phenomenon of precedent. His aphorisms are presented as short sentences and extended constructions, verbalizing affirmations or negations, rhetorical statements, and affective appeals. An ironic or mockingly ironic tone is evident in the depiction of the enemy, along with speech genres of appeals, imperatives, warnings, sympathy, and guidance drawn from the author’s generalized experience. The heroism of war is expressed through preferential comparative axiological structures with core phrases such as “better... than...”. The aphorisms manifest as calls, imperatives, warnings, sympathy, and counsel, summarizing the experience of the Ukrainian people. They are imbued with intimate meanings that portray the writer as a person who believes in victory over the Nazis, a bright future for Ukraine, and the strength of the Ukrainian people, showcasing its mental traits while revealing a degree of disdain toward “khokhols” and the historical enemy of Ukraine, the Moscovites. The image of war in O. Dovzhenko’s work is shown to transform into a triad: synchronicity (present), perspective and prognostication (future, the writer’s prophecy), and retrospection (a look into the past), presenting O. Dovzhenko as an elite linguistic personality of the Ukrainian nation.